PENGARUH KOMUNIKASI INTERPERSONAL, KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN BANK MANDIRI KC JAKARTA KOTA - Astri Susanti Noor; Salman Paludi (Human Capital Development, 2019)
Purpose- This study aims to determine the effect of interpersonal communication, compensation, and motivation on job satisfaction of employee of Bank Mandiri Branch of Jakarta Kota. The type of data in this study are primary or data derived from respondents. Design/methodology/approach- Dara collection can be done through a questionnare instrument. The population in this study were all employees in the Bank Mandiri area of Branch Jakarta Kota with a sample of 100 respondents and were randomly selected (Purposive Sampling), the method of anaysis used descriptive and quantitative methods. Findings- From the results of research on partial variables, the value of t arithmetic is greater than t table, then Ha shows and states there is a positive and significant effect between interpersonal communication, compensation, and motivation on job satisfaction. While the percentage of influence on interpersonal communication, compensation and motivation provided to employees of Bank Mandiri KC Jakarta Kota is 20,16. While the rest is influenced by other variables such as work environment factors and leadership style.